Imagining island food system futures with Indigenous foods: A tok stori on the origins and potential of traditional food systems in Solomon Islands - Wate, Jillian Tutuo; Tikai, Pitakia; Sanau, Lyndellar; Notere Boso, Delvene; Ride, Anouk; Siota, Faye Aborina; Eriksson, Hampus (WorldFish, 2023)
A forum on Island food systems in transition: Strengthening Indigenous food systems in Solomon Islands was hosted on 31 May 2023 by WorldFish and Kastom Gaden Association. This forum brought together rural actors and key stakeholders to talk about traditional farming and aquatic foods under a nutrition-sensitive approach and to listen to ideas about what the Solomon Islands food systems future could look like.